A relação entre desenvolvimento rural e acidentes de trabalho no meio rural nas microrregiões de Chapecó, Concórdia e Xanxerê no Estado de Santa Catarina - Begnini, Sergio (2014)
In this study the rural development was understood as a process that involves several dimensions and sectors which together allow the generation of changes in order to satisfy the population's needs. However the occurrence of rural occupational accidents can be a factor that influences negatively such development. The objective of the study is to associate rural development with the occurrence of rural work-related accidents, in the period 2008-2013, in the micro-regions of Chapecó, Concordia and Xanxerê in the state of Santa Catarina. This is a descriptive study with quantitative approach and applied nature. Data from official agencies of Santa Catarina and Brazil. In rural development, the variables used refer to environmental issues, demographic, economic, social and political-institutional issues. As for accidents rural labor data refer to the age and sex of the victim, the date and place of accident and the classification in ICD-10. From the data collected, through factor analysis, we prepared the index and the degree of rural development for each municipality and by the simple arithmetic average of the average of accidents for each county was calculated. After, through the linear coefficient of Pearson, it was calculated the correlation between the development degree and the average of accidents. In the microregions of Chapecó and Concordia was the municipality considered polo that presented the highest degree of development as well as the highest average accidents, however in the northeast of the municipality has not provided polo Xanxerê the greatest degree of rural development or the highest average of accidents in rural work. The results show evidence that the greater the degree of rural development, the greater the average rural labor accidents, however the level of calculated correlation was low, it difficult the perception of a linearity between the variables, due to the limitations of data, especially in relation to records of rural work accidents.